Polyadenylation of Maternal RNA of Sea Urchin Eggs After Fertilization - Wilt, Fred H. (1973)
Between fertilization, or parthenogenetic activation, and the two-cell stage, the content of polyadenylic acid in sea urchin eggs doubles, and the increase occurs primarily in the ribosome-polyribosome fraction. The increase is due to polyadenylation of preexisting RNA molecules synthesized during oogenesis. The polyadenylation occurs in activated, enucleated merogons. It is argued that cytoplasmic polyadenylation may play a role in mobilization of maternal messenger RNA for translation and the polyadenylic acid does not subserve an exclusively nuclear function.